Soluble E-selectin in cardiovascular disease and its risk factors - Roldán, Vanessa; Marín, Francisco; Lip, Gregory Y. H.; Blann, Andrew D. (Thrombosis and Haemostasis, 2003)
The initial steps in the pathogenesis of atherosclerosis involve changes to the vascular endothelium, which produces numerous substances involved in the regulation and maintenance of vascular integrity and the homeostasis of the coagulation/fibrinolysis system. A further change in endothelial physiology is an increase in the surface expression of cell adhesion molecules, such as E-selectin, which regulate adhesive interactions between certain blood cells and endothelium. As E-selectin is only expressed on activated endothelium, it therefore provides an opportunity to study pathophysiological aspects of this cell in cardiovascular and other disease. However, a soluble form of E selectin (i.e. sE-selectin) can be found in the plasma. This review will focus on sE-selectin, and its potential role in the pathogenesis of cardiovascular disease as raised levels have been found in hypertension, diabetes and hyperlipidemia, although its association in established atherosclerosis disease and its value as a prognostic factor is more controversial.Search strategy: We performed a keyword search (listed above) using electronic databases (PUB-MED, MEDLINE, EMBASE, DARE), and additionally, abstracts from national and international cardiovascular meetings were studied to identify unpublished studies. Relevant authors of these studies were contacted to obtain further data.
Keywords: Soluble E selectin; atherosclerosis; diabetes; smoking; coronary artery disease; peripheral artery disease; hypertension; hyper-cholesterolaemia